2022
DOI: 10.3390/ijerph19148743
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhizic Acid Attenuates Pulmonary Fibrosis of Silicosis by Inhibiting the Interaction between HMGB1 and BRG1 through PI3K/Akt/mTOR Pathway

Abstract: Purpose: High mobility group protein 1 (HMGB1) is a highly conserved DNA-binding nuclear protein that participates in the occurrence and development of silicosis. HMGB1 binds to its specific receptor and activates phosphatidylinositol 3-kinase (PI3K)/protein kinase B, (PKB; Akt)/mammalian target of rapamycin (mTOR) pathway. Brahma-related genes 1 (BRG1; SMARCA4) is the core subunit of SWI/SNF. HMGB1 activates the Akt pathway through BRG1 to promote the proliferation of prostate cancer. Glycyrrhizic acid is a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
2
4
0
Order By: Relevance
“…2 ), suggesting that BRG1 may act as a positive mediator of fibrotic responses downstream of TGF-β1. Consistent with our study, Gong et al [ 16 ], Niu et al [ 37 ], Yang et al [ 38 ] have found that BRG1 is a downstream of TGF-β1 in various cell types. Of note, we also notice that the mRNA level of BRG1 cannot be augmented by TGF-β1 stimulation (data not shown), implying that TGF-β1 might regulate the expression of BRG1 in a post-transcriptional pathway manner in peritoneal mesothelial cells.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…2 ), suggesting that BRG1 may act as a positive mediator of fibrotic responses downstream of TGF-β1. Consistent with our study, Gong et al [ 16 ], Niu et al [ 37 ], Yang et al [ 38 ] have found that BRG1 is a downstream of TGF-β1 in various cell types. Of note, we also notice that the mRNA level of BRG1 cannot be augmented by TGF-β1 stimulation (data not shown), implying that TGF-β1 might regulate the expression of BRG1 in a post-transcriptional pathway manner in peritoneal mesothelial cells.…”
Section: Discussionsupporting
confidence: 93%
“…2), suggesting that BRG1 may act as a positive mediator of fibrotic responses downstream of TGF-β1. Consistent with our study, Gong et al [16], Niu et al [37], Yang et al [38] have found that BRG1 is a downstream of TGF-β1 in various cell types. Of Co-immunoprecipitation demonstrated that the interaction between BRG1 and H3K14ac was decreased after the mutation of BRG1 N1540.…”
Section: Discussionsupporting
confidence: 92%
“… 37 When the cell is stimulated by various kinds of damage, it releases itself into the extracellular space as a damage-associated molecular pattern (DAMP) molecule that participates in inflammatory responses, differentiation and migration of cells. 38 , 39 HMGB1, as a pathogenic factor in DN, interacts with TLRs and RAGE, which are its receptors on the cytomembrane, activating innate immune responses by promoting nuclear translocation of transcription factors. 40 , 41 , 42 Interestingly, high levels of HMGB1 in serum from patients with DN can induce podocyte autophagy, apoptosis, and EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylated AKT enhances the nuclear transcription of NFκB and the release of pro-inflammatory cytokines, and these effects are blocked by PI3K inhibitors, thereby inhibiting hepatocyte apoptosis, reducing inflammation, and alleviating liver damage ( Gong et al, 2020 ). Glycyrrhizic acid ( Niu et al, 2022 ), scoparone ( Liu et al, 2020 ), isorhamnetin ( Li et al, 2015 ), quercetin ( Yang et al, 2020 ), and luteolin ( Jiang et al, 2023 ) have been reported to regulate the PI3K/AKT axis to improve ALI. And these metabolites were detected in YCSND in our study.…”
Section: Discussionmentioning
confidence: 99%